HUBUNGAN TIDAK SARAPAN PAGI, JENIS MAKANAN DAN MINUMAN YANG MEMICU ASAM LAMBUNG DENGAN KEJADIAN DISPEPSIA PADA REMAJA USIA 15-19 TAHUN DI KELURAHAN BANGKINANG - Ade Dita Puteri; Devina Yuristin (KOLONI, 2022)
Dyspepsia caused by bad habits such as not having breakfast, the habit of consuming food and drinks, such as eating spicy, sour, drinking coffee, and carbonated drinks. Breakfast for teenagers is very important because when they are active they need a lot of energy and calories and if they consume too often and drinks that can trigger food acids, it will cause dyspepsia. Data in Kampar Regency in 2021 the number of dyspepsia cases is 9120 cases, Bangkinang Village is 122 cases. The purpose of this study was to determine the relationship between skipping breakfast, types of food and beverages that trigger stomach acid with the incidence of dyspepsia in adolescents aged 15-19 years in Bangkinang village in 2021. This type of research is descriptive correlation with cross sectional research design. The population of this study was 488 adolescents aged 15-19 years who lived in Bangkinang Village. By displaying the sample using simple random sampling. From the Chi-Square test, it was found that there was a relationship between not having breakfast, the type of food and drink that triggers stomach acid and the incidence of dyspepsia (pv = 0.001). Research provides information from health workers to the public about the importance of the morning and the importance of choosing the types of food and drinks that are good for stomach health. Keywords: breakfast, food, drink, gastric acid trigger, dyspepsia